An analysis of sleep complaints on Sina Weibo. (September 2016) - Tian, Xianyun; Yu, Guang; He, Fang
Abstract: This study explores sleep complaints on Sina Weibo to gain insights into social networking about mental health. A random sample (n = 1000) of insomnia-related postings was coded and analyzed to investigate the themes and symptoms expressed in postings. The most common theme mentioned is the disclosure of insomnia. The difficulty with sleep initialization is the most common symptom revealed in postings. Besides, the prevalence of insomnia is higher in certain areas and the people who may suffer from insomnia tend to be active from midnight to noon. Our findings can be used to detect and provide help for those Weibo users who may suffer from insomnia.